New heuristic algorithms for solving the planar p-median problem. (October 2015) - Drezner, Zvi; Brimberg, Jack; Mladenović, Nenad; Salhi, Said
Abstract: In this paper we propose effective heuristics for the solution of the planar p -median problem. We develop a new distribution based variable neighborhood search and a new genetic algorithm, and also test a hybrid algorithm that combines these two approaches. The best results were obtained by the hybrid approach. The best known solution was found in 466 out of 470 runs, and the average solution was only 0.000016% above the best known solution on 47 well explored test instances of 654 and 1060 demand points and up to 150 facilities.